2010
DOI: 10.1111/j.1439-0442.1975.tb01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Changes in the Endometrium of the Goat

Abstract: Summary A study was made of the micromorphological features of the endometrium of the goat (intercaruncular area). During the luteal phase of the oestrous cycle the lamina epithelialis was pseudostratified columnar, and the fibrillar elements of the endometrial stroma were mainly of the reticular kind. During pregnancy the endometrium became more folded and decreased in thickness as pregnancy advanced. The lamina epithelialis was denuded at the first month of pregnancy and restored itself in horns containing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The findings presented here were based on the histochemical examination of 16 gravid uteri of Balady goats, using the same material as was used by BADAWI et al (1974) for a histomorphological study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings presented here were based on the histochemical examination of 16 gravid uteri of Balady goats, using the same material as was used by BADAWI et al (1974) for a histomorphological study.…”
Section: Methodsmentioning
confidence: 99%
“…The role of the endometrium in the establishment of pregnancy at its early stages and in maintaining it during the rest of gestation cannot be neglected. It has been demonstrated that the endometrium in the goat undergoes certain histological changes during pregnancy (BADAWI, FATEH EL-BAB and KAMEL, 1974).…”
Section: Introductionmentioning
confidence: 99%